Concepts and Challenges in the Implementation of Talent Management in Improving Employee Performance at the Company - Darmilisani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine and analyze the effect of implementing talent management which consists of workforce preparation, workforce development and workforce management on employee performance through employee engagement. Talent management is one of the important issues that has become a topic of conversation in the world of human resource management. This is a logical consequence of the limited availability of talent, while the need for them continues to increase. One of the signs of this era is increasingly fierce business competition, including the necessity for local companies to compete with companies from regional and even global environments. Every company wants to dominate business and market competition. In realizing this there are three assets that must be owned by a company, namely financial capital, products and labor, but among the three most important assets is the workforce they have. Companies must be able to get and retain the best employees.